Synthetic panics : the symbolic politics of designer drugs - Jenkins, Philip, 1952- (New York University Press, 1999)
America has a long history of drug panics in which countless social problems have been blamed on the devastating effects of some harmful substance. In the last forty years, such panics have often focused on synthetic or designer drugs, like methamphetamine, PCP, Ecstasy, methcathinone, and rave drugs like ketamine, and GHB. Fear of these substances has provided critical justification for the continuing "war on drugs." Synthetic Panics traces the history of these anti-drug movements, demonstrating that designer chemicals inspire so much fear not because they are uniquely dangerous, but because they bring into focus deeply rooted public concerns about social and cultural upheaval. Jenkins highlights the role of the mass media in spreading anti-drug hysteria and shows how proponents of the war on drugs use synthetic panics to scapegoat society's "others" and exacerbate racial, class, and intergenerational conflict
Keywords: Drug control -- United States.; Designer drugs -- Government policy -- United States.; Drug abuse -- United States.; Designer drugs.; Drug addiction.; Drug abuse.; Drug and Narcotic Control; Designer Drugs; Substance-Related Disorders; United States; Lutte antidrogue -- États-Unis.; Drogues de confection -- Politique gouvernementale -- États-Unis.; Toxicomanie -- États-Unis.; Drogues de confection.; Toxicomanie.; drug abuse.; drug addiction.; SOCIAL SCIENCE -- General.; BUSINESS & ECONOMICS -- Infrastructure.; Drug addiction; Designer drugs; Designer drugs -- Government policy; Drug abuse; Drug control; Synthetische Droge; Drogenpolitik; USA; Electronic books.